Holistically Managing Pathogens and Nutrients in Urbanizing Tropical Towns: Can Sanitation Technologies Create Safer Conditions for Beach Recreation? - Orner, Kevin (2021)
Rapidly urbanizing coastal communities are prone to overpopulation and unrestrained growth that result in pathogen and nutrient emissions, which impair beach water quality and jeopardize human and environmental health. Decision makers face complex, context-dependent choices when selecting sanitation technologies with varying abilities to remove pathogens and nutrients. The goal of this study was to identify context-appropriate sanitation solutions that manage pathogens and nutrients to ensure safe beach swimming conditions in an urbanizing coastal town that relies on tourism. Quantitative microbial risk assessment was utilized to determine the pathogen log10 reduction values (LRVs) required for safe swimming. A lack of consensus in the literature about an aggregation parameter in the norovirus dose−response model resulted in predicted LRVs that differed by as much as 3 orders of magnitude. Local experts identified nine context-appropriate infrastructure scenarios, and their ability to reduce pathogen and nutrient loadings was modeled. The model showed that spatially targeted sanitation infrastructure scenarios could effectively meet LRV targets. Seasonal increases in population were predicted to greatly impact pathogen and nutrient loadings. Top-performing scenarios that managed both pathogens and nutrients included centralized treatment with disinfection and integrated resource recovery. Future research is needed to understand the scenarios’ sociocultural feasibility and costs.